An Examination of the Conditional and Unconditional Relations Between Risk and Return on the Kuala Lumpur Stock Exchange - Haniff, Mohd Nizal (2000)
Previous empirical tests of the Capital Asset Pricing Model (CAPM) in mature and emerging capital markets focused on the premise that there is a positive linear relationship between portfolio betas and portfolio returns. The CAPM predicts that the expected return for any asset is a positive function of only three variables namely, beta (the covariance of asset return and market return), the risk free rate and the expected market return. Earlier findings by Black, Jensen and Scholes (1972) and Fama and MacBeth (1973) in the US stock markets generally found a weak but positive relationship between portfolio returns and beta over the entire sample periods. However, this assertion was seriously challenged by the findings of Banz (1981) and Fama and French (1992) which evidence indicated the absence of a systematic relationship between beta and portfolio returns. Further evidence indicated that other variables such as size of the finn and the ratio of the book value of a finn's common equity to its market value seemed to do better than beta in explaining the cross-sectional variations in average asset returns. Pettengill, Sundaram and Mathur (1995) offered a new interpretation of systematic relationship and introduced a new methodology to test the CAPM, which assumes a conditional relationship between portfolio returns and beta depending on whether the excess market return is positive or negative. The main objective of the study is to examine this conditional relationship between beta and returns as proposed by Pettengill, Sundaram and Mathur (1995) to Malaysian stock returns. To study this relationship, monthly data for a period of 15 years between January 1985 and December 1999 were used. The study also looked at the impact of non-synchronous trading problem on the KLSE. In addition, the study also examined the impact of portfolio size on the systematic and conditional as well as unconditional relationships between beta and portfolio returns. The results indicated that there was a very weak evidence of a significant risk premium on beta when the unconditional relationship between beta and portfolio returns was considered. When the sample was split into periods whether the excess market return is positive or negative, there was a significant relationship between portfolio returns and beta. The evidence also indicated that the size of portfolio had a positive linear relationship with' the value of the cross-sectional coefficient under conditional relationship. However, the results did not support any positive reward for holding market risk during the sample period.